Evaluation of three parasite lactate dehydrogenase-based rapid diagnostic tests for the diagnosis of falciparum and vivax malaria. - Ashley, E; Touabi, M; Ahrer, M; Hutagalung, R; Htun, K; Luchavez, J; Dureza, C; Proux, S; Leimanis, M; Lwin, M; Koscalova, A; Comte, E; et al. (BioMed Central, 2009)
BACKGROUND: In areas where non-falciparum malaria is common rapid diagnostic tests (RDTs) capable of distinguishing malaria species reliably are needed. Such tests are often based on the detection of parasite lactate dehydrogenase (pLDH). METHODS: In Dawei, southern Myanmar, three pLDH based RDTs (CareStart Malaria pLDH (Pan), CareStart Malaria pLDH (Pan, Pf) and OptiMAL-IT)were evaluated in patients presenting with clinically suspected malaria. Each RDT was read independently by two readers. A subset of patients with microscopically confirmed malaria had their RDTs repeated on days 2, 7 and then weekly until negative. At the end of the study, samples of study batches were sent for heat stability testing. RESULTS: Between August and November 2007, 1004 patients aged between 1 and 93 years were enrolled in the study. Slide microscopy (the reference standard) diagnosed 213 Plasmodium vivax (Pv) monoinfections, 98 Plasmodium falciparum (Pf) mono-infections and no malaria in 650 cases. The sensitivities (sens) and specificities (spec), of the RDTs for the detection of malaria were- CareStart Malaria pLDH (Pan) test: sens 89.1% [CI95 84.2-92.6], spec 97.6% [CI95 96.5-98.4]. OptiMal-IT: Pf+/- other species detection: sens 95.2% [CI95 87.5-98.2], spec 94.7% [CI95 93.3-95.8]; non-Pf detection alone: sens 89.6% [CI95 83.6-93.6], spec 96.5% [CI95 94.8-97.7]. CareStart Malaria pLDH (Pan, Pf): Pf+/- other species: sens 93.5% [CI95 85.4-97.3], spec 97.4% [95.9-98.3]; non-Pf: sens 78.5% [CI95 71.1-84.4], spec 97.8% [CI95 96.3-98.7]. Inter-observer agreement was excellent for all tests (kappa > 0.9). The median time for the RDTs to become negative was two days for the CareStart Malaria tests and seven days for OptiMAL-IT. Tests were heat stable up to 90 days except for OptiMAL-IT (Pf specific pLDH stable to day 20 at 35 degrees C). CONCLUSION: None of the pLDH-based RDTs evaluated was able to detect non-falciparum malaria with high sensitivity, particularly at low parasitaemias. OptiMAL-IT performed best overall and would perform best in an area of high malaria prevalence among screened fever cases. However, heat stability was unacceptable and the number of steps to perform this test is a significant drawback in the field. A reliable, heat-stable, highly sensitive RDT, capable of diagnosing all Plasmodium species has yet to be identified.